Firm Attributes and Tax Avoidance of Nigerian Oil and Gas Firms: Moderating Role of Managerial Ownership - Udisifan Michael Tanko; Suleiman Lawan Waziri; Aminu Yusuf (Journal of Accounting Research, Organization and Economics, 2022)
The study examined the moderating effect of managerial ownership on the relationship between firm attributes and tax avoidance in Nigerian listed oil and gas firm for the period of 2011-2020. Secondary data were extracted from the financial reports and accounts of the companies. The study employed Generalized Least Square (GSL) estimator of the regression model. Study revealed that leverage has positive significant effect on tax avoidance. The study reported that board financial expertise has positive and significant impact on tax avoidance. The study documented that managerial ownership has significant positive impact on tax avoidance. Similarly, managerial ownership positively and significantly moderates the relationship between firm size and tax avoidance. The study recommends that, the board of directors in the oil and gas firms in Nigeria should ensure that shareholding of the insider managers is increase in such a way that the proportion of their shareholding should be minimal which should not be less than 20% of the total shareholding in the company as it was found being among the factors that increase tax avoidance. Doing this will encourage managers to put more effort to work toward improving firm performance. The study also recommends that as leverage improve tax avoidance, firms should obtain more debt than equity to advantage of interest on loan which is tax deductible. Since board financial expertise increase tax avoidance, firm should encourage for inclusion of financial expertise as member of board of director in order to take decision on tax issues which will benefit the company.